Rancang Bangun Sistem Informasi Manajemen Aset di Yayasan Perguruan Tinggi Flores (YAPERTIF) - Rainarius Gale Goa; Ferdinandus Lidang Witi; Melky Radja (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
The development of technology is getting faster so that it forces people to use information Information Technology has had a tremendous impact, especially in the field of management. The old system is gradually being replaced by a newer system as a result of the development of increasingly advanced information technology, one of which is the use of a Management Information System which has become a necessity in an agency. Management information systems are typically used to process data, make information accurate, improve performance, and perform as expected. Asset management in Yapertif is less effective and efficient because it still uses Ms. Excel, which takes a long time to manage and search for asset data. when a large amount of data or asset information is needed, for example during accreditation or a request from Dikti, it takes more time to search. The solution to overcome the existing problems, the researchers took a study with the title "Design of an Asset Management Information System at the Flores Higher Education Foundation (Yapertif)". The development of the system itself will use the Waterfall method and the testing technique uses Blackbox testing. The asset management information system that is built is expected to make asset management more efficient and structured, as well as facilitate data collection on the number of assets, data collection on assets based on their condition, grouping of assets by type and facilitate tracking of asset data in Yapertif.